2017
DOI: 10.1080/00365521.2017.1334813
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic findings, incidence and characteristics of microscopic colitis in a large cohort of patients from the United Kingdom

Abstract: One in six patients with MC demonstrated distinct macroscopic findings at colonoscopy. Our data confirm a female preponderance in MC, a relatively short symptom duration and use of certain drugs as common features. Both right- and left-sided biopsies were frequently positive, suggesting flexible sigmoidoscopy and biopsy could confirm a diagnosis in certain individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 59 publications
5
34
1
Order By: Relevance
“…One recent Swedish study reported endoscopic abnormalities in 37% of patients with CC and 25% of patients with LC [18]. The frequency of endoscopic abnormality in this study (15%) is very similar to that found in another recent UK study [17]. We accept, however, that recording information on endoscopic appearances from pathology request forms alone may result in incomplete data collection.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…One recent Swedish study reported endoscopic abnormalities in 37% of patients with CC and 25% of patients with LC [18]. The frequency of endoscopic abnormality in this study (15%) is very similar to that found in another recent UK study [17]. We accept, however, that recording information on endoscopic appearances from pathology request forms alone may result in incomplete data collection.…”
Section: Discussionsupporting
confidence: 83%
“…This is the first cohort of patients with MC reported within the Northern Ireland population. We describe a population-representative series of patients with CC and LC whose demographic and clinical features are similar to previously reported larger series from the UK and Ireland [17,24]. Our incidence data for LC are likely to be incomplete, but the average annual incidence of CC (5.0 per 100 000) is similar to that observed in other epidemiological studies from the UK and further afield [2,17].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Patients with CC, LC and MCi cannot be distinguished from each other based on their demographic features, clinical characteristics or symptom presentation 23–25. Treatment guidelines do not distinguish between CC and LC,9 because differences in treatment outcomes have not been observed between these subgroups 26.…”
Section: Diagnosis Requires Histological Examination Of Colonic Bimentioning
confidence: 99%